2012
DOI: 10.1016/j.polymer.2011.10.063
|View full text |Cite
|
Sign up to set email alerts
|

Establishment, morphology and properties of carbon nanotube networks in polymer melts

Abstract: As for nanofillers in general, the properties of carbon nanotube (CNT) -polymer composites depend strongly on the filler arrangement and the structure of the filler network. This article reviews our actual understanding of the relation between processing conditions, state of CNT dispersion and structure of the filler network on the one hand, and the resulting electrical, melt rheological and mechanical properties, on the other hand. The as-produced rather compact agglomerates of CNTs (initial agglomerates, >1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
357
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 491 publications
(377 citation statements)
references
References 97 publications
15
357
4
1
Order By: Relevance
“…It was found, that the resistance shows an oscillating response as well, where the frequency of the electrical oscillations is twice as fast the frequency of the deformation. This finding was also confirmed qualitatively by Alig et al [2] and Zeiler et al [12] for polycarbonate filled with carbon nanotubes. Zeiler et al [12] measured the oscillating electrical conductivity for different strain amplitudes and for different molar masses of the matrix polymer.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…It was found, that the resistance shows an oscillating response as well, where the frequency of the electrical oscillations is twice as fast the frequency of the deformation. This finding was also confirmed qualitatively by Alig et al [2] and Zeiler et al [12] for polycarbonate filled with carbon nanotubes. Zeiler et al [12] measured the oscillating electrical conductivity for different strain amplitudes and for different molar masses of the matrix polymer.…”
Section: Introductionsupporting
confidence: 78%
“…The electrical properties of polymers are dramatically influenced by the incorporation of conductive fillers, such as carbon black or carbon nanotubes [1,2]. To produce conductive polymer composites for industrial applications, melt processing techniques such as extrusion or injection moulding are usually used.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of a conductive network in the internal core leads to a conductive path, which can explain the before discussed electrical properties [16]. Consequently, it is possible to conclude that the skin layers, covering the external regions, are characterized by a low conductivity, while the core region already becomes conductive at low filler content.…”
Section: -2mentioning
confidence: 72%
“…Detailed work by Alig and co-workers has shed light on the mechanisms of the formation of the CNT network in the matrix melt [1]. Zeiler et al found that the network formation is enhanced by a matrix of lower molar mass and at higher temperature [2].…”
Section: Introductionmentioning
confidence: 99%